The determinants of irrigation participation and its impact on the pastoralist and agro-pastoralists income in Ethiopia: A review study - Dagninet Asrat; Adugnaw Anteneh (Cogent Food & Agriculture, 2019)
This review identified factors that determine the decision of a household to participate in irrigation, and its impact on the income of pastoralists and agro-pastoralists. In Ethiopia, agriculture is the basic economic sector in which the country relies for its social and economic development. In Ethiopia, the majority of population directly or indirectly engaged in agriculture where around 95% of the country’s agricultural output is produced by smallholder farmers. However, the sector has remained in its rudimentary stage, especially in dry lands of Ethiopia. The recurrent drought is the key factor, causes vulnerability to agro-pastoralists and pastoralists. To alleviate the problem, the government of Ethiopia has taken irrigation agriculture subsector as the main strategies in the overall country’s development agenda and gives high priority to irrigation development, including smallholder and large-scale commercial schemes to exploit the untapped resources. Ethiopia is considered as the water tower of Africa. However, currently, only 5% is actually irrigated, which is very low. The basic factors influencing the decision of smallholder farmers to participate in irrigation farming are demographic, socioeconomic and institutional characteristics. Hence, to make considerable improvement on the decision to adopt irrigation, actions should be taken by household heads, government of Ethiopia, national and international organizations.